Step
*
2
1
1
of Lemma
reg-seq-nexp_wf
1. x : ℝ
2. k : ℕ+
3. 1 ≤ 2^k - 1
4. v : {k:{3...}| ∀n:ℕ+. (|x n| ≤ (n * k))} 
5. canon-bnd(x) = v ∈ {k:{3...}| ∀n:ℕ+. (|x n| ≤ (n * k))} 
6. 1 ≤ 2^(k - 1)
⊢ (k * ((v^(k - 1) ÷ 2^(k - 1)) + 1)) + 1-regular-seq(reg-seq-nexp(x;k))
BY
{ (RepeatFor 2 ((D 0 THENA Auto))
   THEN RepUR ``reg-seq-nexp`` 0
   THEN (RWW "exp-fastexp<" 0 THENA Auto)
   THEN D 4
   THEN (Assert ∀n:ℕ+. (|x n| ≤ (n * v)) BY
               (Unhide THEN Auto))
   THEN Thin (-6)
   THEN (InstLemma `div_bounds_1` [⌜v^(k - 1)⌝;⌜2^(k - 1)⌝]⋅ THENA Auto)
   THEN (Assert 0 ≤ (k * ((v^(k - 1) ÷ 2^(k - 1)) + 1)) BY
               Auto)) }
1
1. x : ℝ
2. k : ℕ+
3. 1 ≤ 2^k - 1
4. v : {3...}
5. canon-bnd(x) = v ∈ {k:{3...}| ∀n:ℕ+. (|x n| ≤ (n * k))} 
6. 1 ≤ 2^(k - 1)
7. n : ℕ+
8. m : ℕ+
9. ∀n:ℕ+. (|x n| ≤ (n * v))
10. 0 ≤ (v^(k - 1) ÷ 2^(k - 1))
11. 0 ≤ (k * ((v^(k - 1) ÷ 2^(k - 1)) + 1))
⊢ |(m * ((x n)^k ÷ (2 * n)^(k - 1))) - n * ((x m)^k ÷ (2 * m)^(k - 1))| ≤ ((2
  * ((k * ((v^(k - 1) ÷ 2^(k - 1)) + 1)) + 1))
  * (n + m))
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  k  :  \mBbbN{}\msupplus{}
3.  1  \mleq{}  2\^{}k  -  1
4.  v  :  \{k:\{3...\}|  \mforall{}n:\mBbbN{}\msupplus{}.  (|x  n|  \mleq{}  (n  *  k))\} 
5.  canon-bnd(x)  =  v
6.  1  \mleq{}  2\^{}(k  -  1)
\mvdash{}  (k  *  ((v\^{}(k  -  1)  \mdiv{}  2\^{}(k  -  1))  +  1))  +  1-regular-seq(reg-seq-nexp(x;k))
By
Latex:
(RepeatFor  2  ((D  0  THENA  Auto))
  THEN  RepUR  ``reg-seq-nexp``  0
  THEN  (RWW  "exp-fastexp<"  0  THENA  Auto)
  THEN  D  4
  THEN  (Assert  \mforall{}n:\mBbbN{}\msupplus{}.  (|x  n|  \mleq{}  (n  *  v))  BY
                          (Unhide  THEN  Auto))
  THEN  Thin  (-6)
  THEN  (InstLemma  `div\_bounds\_1`  [\mkleeneopen{}v\^{}(k  -  1)\mkleeneclose{};\mkleeneopen{}2\^{}(k  -  1)\mkleeneclose{}]\mcdot{}  THENA  Auto)
  THEN  (Assert  0  \mleq{}  (k  *  ((v\^{}(k  -  1)  \mdiv{}  2\^{}(k  -  1))  +  1))  BY
                          Auto))
Home
Index